EGFR testing in paraffin-embedded cell block cytology material is reliable with increased detection for effusion fluid. (December 2022) - Man Ng, Joanna Ka; Chow, Chit; Kin Chan, Ronald Cheong; Pang Chan, Ka; Xi Li, Joshua Jing; Ching Li, Molly Siu; To, Ka-Fai
Highlights: Cell block cytology material is reliable for EGFR testing with high concordance. Cytology material showed lower adequacy rates than biopsy or excision specimens. Effusion fluid had the highest mutation detection rate among all cytology specimens and was superior to pleural biopsy. EGFR mutation detection rate for lung and lymph node aspirates were non-inferior to tissue biopsy or excision. Abstract: Introduction: Cytology is integral to lung cancer diagnosis. Aspiration and exfoliative fluid specimens represent valuable tumor material for molecular testing. In this study, a large retrospective cohort of EGFR tests was reviewed to address the adequacy, detection and discrepancy rate in tests performed with cytology material. Methods: EGFR tests performed from 2013 to 2022 were reviewed and classified by the modality of obtaining tissue and by tissue type. EGFR tests for tissue specimens were performed on unstained sections of paraffin-embedded material on glass slides. Adequacy and types of mutation(s) detected were analysed. Cases where multiple EGFR testing was performed on the same patient were reviewed for discordance. Results: There were 5, 504 tests retrieved, with 1, 855, 3, 607 and 42 performed on cytology, surgical and blood specimens. Lung and excision specimens were more often adequate (p < 0.001). Cytology material showed lower adequacy rates (p < 0.01). EGFR detection (positive) rate was higher in pleural fluid compared to biopsy (59.8 % vs 50.7 %, p = 0.022), but similar between lung and lymph node cytology and non-cytology specimens. Effusion fluid specimens had the highest adequacy (81.5 %) and detection rate (59.3 %) among cytology specimens (p < 0.001). Four (4.4 %) cases showed discordant results in cytology specimens. Two were false negatives in the non-cytology material. Only in one case was cytology material genuinely discrepant. The remaining discordance was attributed to the interval treatment effect. Conclusion: The findings support that EGFR testing in cell block is reliable and complements tissue material. In addition, pleural fluid appears to be superior to pleural biopsies for molecular testing.